Double-crosslinked nanocomposite hydrogels for temporal control of drug dosing in combination therapy. (1st April 2020) - Wu, Can; Liu, Jing; Zhai, Ziran; Yang, Liqiang; Tang, Xuan; Zhao, Lingzhi; Xu, Keming; Zhong, Wenying
Abstract: Temporal control of drug dosing is indispensable for a successful combination therapy that utilizes cisplatin (CDDP) and irinotecan (IRN), with clinical evidence supporting a higher response rate when CDDP was administered prior to IRN. Herein, a peptide-based nanocomposite hydrogel ( CDDP/Pept-AlgNP/IRN ) was designed for differential release of CDDP and IRN to maximize synergism of two drugs. First, a double-crosslinking strategy was exploited for structural reinforcement of hydrogel, with integration of coordination interactions between CDDP and hydrogelator (Pept) as well as electrostatic interactions between Pept and alginate nanoparticles (AlgNP/IRN), that afforded nanocomposite hydrogel with 42-fold increase in storage modulus comparing to peptide gel alone. Next, the nanocomposite hydrogel with excellent injectability served as a depot for controlled release of dual drugs, and guaranteed a fast release of CDDP prior to a tunable release of IRN that is dependent on fraction ratios of AlgNP in the composite materials. Comparing to simple mixture of CDDP and IRN solution, CDDP/Pept-AlgNP/IRN hydrogel formulation demonstrated excelling synergism of CDDP and IRN in cell inhibition studies, with efficacious antitumor potency further proved in tumor regression studies in vivo . We believe that the strategy of utilizing co-assembly of multiple pairs of entities ( i.e. drug-gelator, nanoparticle-gelator) in composite materials provides a generalized method to design mechanically stable supramolecular hydrogels, and further promises an exact temporal control of drug dosing by packing individual drugs in co-assembled structures/domains to satisfy clinical demands from combination therapy. Statement of Significance: This study reports the design of nanocomposite hydrogels with two distinct co-assembling domains for structural reinforcement of hydrogel and differential release of two drugs (CDDP and IRN) in combination therapy. We first investigated the effects of co-assembling processes for the reinforcement of hydrogel. Then we utilized the hydrogel for differential release of CDDP and IRN to achieve better synergistic efficacy of drugs in inhibiting the growth of cancer cell A549 and better anticancer efficacies than single drug formulations or solution mixtures of dual drugs in an A549-xenografted mouse model. We believe that the strategy of packing individual drugs in distinct co-assembling structures promises a paradigm shift for regulating temporal control of drug dosing in combination therapy. Graphical abstract: Image, graphical abstract